Identity Concealed: Gender Dynamics in We Hunt the Flame (2019) by Hafsah Faizal - Andani, Eddline Kusuma; Kristianto, Bayu (Syntax Literate, 2025)
This study investigates gender dynamics and identity negotiation in Hafsah Faizal’s We Hunt the Flame (2019), focusing on the protagonists Zafira and Nasir as literary representations of resistance against patriarchal expectations. Set in the Middle East-inspired fantasy world of Arawiya, the novel presents Zafira disguising herself as a man to gain autonomy and Nasir concealing his compassion to maintain dominance. The research employs a qualitative method through textual analysis, applying Stuart Hall’s representation theory and Judith Butler’s gender performativity framework to examine how the narrative constructs gender identity and social power. The findings reveal that both characters experience identity suppression as a means of survival, reflecting mechanisms of marginalization akin to those faced by Muslim Americans. Zafira’s rejection of feminine labeling and Nasir’s internal conflict expose the costs of societal compliance, paralleling the experiences of Muslim women navigating stereotypes and Muslim men managing post-9/11 identity tensions. Literary symbols, language choices, and character interactions show how rigid gender roles are challenged within the story. The study argues that the novel critiques patriarchal norms by presenting a narrative where gender performances are survival mechanisms and forms of resistance. By connecting fictional experiences with real-world Muslim identity negotiations, the research contributes to discussions on gender, culture, and representation in contemporary young adult literature. It also opens space for further inquiry into how speculative fiction can serve as a lens for analyzing identity and social critique within marginalized communities.